2014
DOI: 10.1097/hp.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis-block Micronucleus Assay by Manual and Automated Scoring

Abstract: The cytokinesis-block micronucleus assay in peripheral blood lymphocytes is one of the best standardized and validated techniques for individual radiation dose assessment. This method has been proposed as an alternative to the dicentric chromosome assay, which is considered the "gold standard" in biological dosimetry because it requires less time and cytogenetic expertise. Nevertheless, for application as a biodosimetry tool in large-scale nuclear or radiological accidents, the manually performed cytokinesis-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Figure B shows the average calibration curve for the rate of MN per BNC from both Figure A and our previous work . Also plotted in Figure B are calibration curves from Schunck et al , Willems et al , De Sanctis et al , and Thierens et al . These curves were plotted using the quadratic equations provided by the authors and demonstrate the variability between calibration curves using automated slide‐scoring based versions of the CBMN assay.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Figure B shows the average calibration curve for the rate of MN per BNC from both Figure A and our previous work . Also plotted in Figure B are calibration curves from Schunck et al , Willems et al , De Sanctis et al , and Thierens et al . These curves were plotted using the quadratic equations provided by the authors and demonstrate the variability between calibration curves using automated slide‐scoring based versions of the CBMN assay.…”
Section: Resultsmentioning
confidence: 82%
“…(B) The average rate of MN per BNC from A (squares) and the average rate of MN per BNC from our previous work in Rodrigues et al (circles) including error bars which represent the standard error of the mean. The rate of MN per BNC from Schunck et al (solid line), Willems et al (dashed line), De Sanctis et al (dashed‐dotted line), and Thierens et al (dotted line) are also plotted using the equations provided in those publications. (C, D) Estimated dose (Gy) versus delivered dose (Gy) determined by the IS X ‐CBMN method for nine blinded samples using the optimized (circles) and original (squares) IDEAS ® analysis templates following 40 min ( C ) and 5 min ( D ) of data collection.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, their method was able to generate dose estimations to within 0.2 Gy of the delivered dose when scoring blinded samples and they have estimated that their method could allow for the processing of approximately 60 samples in a 12 h period. In 2014, De Amicis et al [62] and De Sanctis [63] used a similar automated slide-scoring method to generate calibration curves and also reported that the number of MN scored at 3 Gy is lower by a factor of 2, similar to the observations of Willems et al, [37] Varga et al [39] and Schunk et al [61] . Still, dose estimations were generated to within 0.3 Gy (or less) of the delivered dose for a number of blinded samples between 0-4 Gy after 8 min of slide scoring time [62,63].…”
Section: Automated Scoring Methodsmentioning
confidence: 66%
“…Willems et al [37] were able to generate dose estimates to within 0.2 Gy of the delivered dose using automated slide-scoring however, only a single dose point (1 Gy) was examined. Additionally, in recent publications by De Amicis et al [62] and De Sanctis [63] dose estimates were generated to within 0.3 Gy (or less) of the delivered dose using automated slide-scoring for a number of doses between 0-4 Gy. The results of the work presented here demonstrates that the ISX-CBMN method, performed using standard culture time and volume conditions, is also able to estimate blinded doses between 0-4 Gy to within 0.3 Gy of the delivered dose and is comparable to results presented in other works using automated slide-scoring versions of the CBMN assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation